Facile, sustainable and unassisted plain water oxidation on Au/Ce0.9Ti0.1O2 nanorods in direct sunlight - Dubey, Anjani; Mishra, Abhaya Kumar; Negi, Sanjay Singh; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2022)
Impressive rate of solar water oxidation to molecular oxygen (O-2) has been demonstrated on nanorods (NRs) of Ce0.9Ti0.1O2 (CT-NR) and Au-deposited CT-NR (Au-CT-NR) photocatalysts with a sacrificial agent (Fe3+) and in plain water in one sun condition, direct sunlight and with lambda >= 455 nm. Probably the highest 0 2 yield of 11 mmol/h.g was observed with Au-CT-NR thin film in plain water in direct sunlight, with no sacrificial agent or applied potential. Photoelectrochemical measurements demonstrate a marked reduction in oxidation onset potential of Au-CT-NR by 150 mV with stable photocurrent (0.75 mA/cm(2)), compared to CT-NR (0.23 mA/cm(2)), indicating the operative of plasmon-induced resonant energy transfer (PIRET) process. Effective electron quenching by nanogold and hence low recombination in the depletion region is a critical step for the observation of a high rate of oxygen evolution. In addition to this, a predominant change in the nature of the valence band from O-2p dominated on CeO2 to Ce-4f dominated with CT-NR (due to Ti4+ introduction in CeO2), the efficient light absorption of photocatalysts in thin-film form, functional and effective PIRET process, and facile E-F alignment, enhances the oxygen evolution with Au-CT-NR in direct sunlight and make it highly sustainable. A possible mechanism of water oxidation is proposed from the observed experimental findings.
Keywords: ceria; Electronic integration; Photocatalysis; thin film; water splitting

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Utilizing nature's endowment: artificial leaf concept for methane activation to C-C coupled ethanol or ethylene - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Avani, Mangaladasan J.; Bajpai, Himanshu; Salgaonkar, Kranti N.; Javaregowda, Bharathkumar H.; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2025)
Methane activation (MA) to platform chemicals under ambient conditions still remains an open challenge to be fully realised. The present work shows the fabrication of CeVO4 quantum dots (CV-QDs) by a bottom-up approach; they are assembled from Ce3+ and metavanadate ions, and structurally and electronically integrated into the micro-/meso-pores of TiO2 (CV-QD-TiO2 (CVT)), demonstrating the conversion of MA to ethanol/ethylene by visible light-driven photocatalysis. CV-QDs in confined pores modify the quantum confinement effects and are characterized by physicochemical methods. The current synthetic strategy is potentially scalable and results in sub-quadrillion heterojunctions in a 1 mg CVT photoanode spread over 1 cm2. MA with CVT under one-sun conditions demonstrates similar to 100% selectivity to ethanol, yielding 4.36 mu mol h-1 cm-2, with a solar-to-fuel efficiency (STFE) of 0.56. Further, by employing a co-catalyst, significant STFE (5.08) and yield (39.5 mu mol h-1 cm-2) are achieved selectively towards ethylene. A deliberate addition of methanol increases the rate of ethanol production by 17.2 times, indicating that the methyl-methoxy interaction is the origin of C-C coupling. Weight is normalized to a gram of CV-QDs in a large area CVT photoanode to yield 109 mmol h-1 gCV-QD-1 of ethanol and 988 mmol h-1 gCV-QD-1 of ethylene. Enhanced activity and selectivity towards the C2-product is attributed to band-edge modulation and trillions of heterojunctions, which in turn facilitate charge separation and charge transfer for effective charge utilisation at redox sites.